Implementasi Pelaksanaan Program Pengembangan Keprofesian Berkelanjutan (PKB) Guru Sekolah Dasar - septiana wulandari; Supriyoko Supriyoko (Universitas Sarjanawiyata Tamansiswa, 2022)
Implementation of the Continuous Professional Development Program (PKB) for Se Dabin 2 State Elementary School Teachers, Central Magelang District, Magelang City. This study aims to describe (1) the implementation of Continuous Professional Development (PKB) for teachers at SD Negeri Se Dabin 2, Magelang Tengah District, Magelang City, (2) reasons for teachers at SD Negeri Se Dabin 2, Magelang Tengah Subdistrict in implementing Continuous Professional Development (PKB), ( 3) the supporting and inhibiting factors faced when participating in Continuous Professional Development (PKB), (4) the efforts of the teachers of SD Negeri Se Dabin 2, Magelang Tengah District in overcoming obstacles in the implementation of Continuous Professional Development (PKB).This study uses a qualitative approach with a descriptive type. Sources of research data are school principals, HR development coordinator, 6 classroom teachers. Data collection techniques using in-depth interviews, observation, and documentation. The data analysis technique uses the Miles and Huberman model, namely data reduction, data display, and drawing conclusions. Test the validity of the data using technical triangulation and source triangulation.The results of the study show that (1) the implementation of PKB includes functional training activities and teacher collective activities, scientific publications and innovative works are quite good, (2) the reason teachers participate in PKB is to improve their professionalism, (3) the supporting and inhibiting factors in the implementation PKB comes from the Office, institutions and themselves, (4) efforts made by teachers in overcoming obstacles are to increase activities in PKB and become more independent teachers.